Relational Frame Theory and Cognitive Defusion: Discussions and directions for experimental research - Mello, Matheus H. S.; Almeida, Paola E. M. (Perspectivas em Análise do Comportamento, 2021)
Relational Frames Theory (RFT) is a behavioral-analytic approach for the study of verbal behavior. Acceptance and Commitment Therapy (ACT) is a therapeutic philosophically based on functional contextualism, and conceptually influenced by RFT and basic behavioral principles. Despite it said to be based on the RFT, many ACT concepts and terms lack conceptually consistent definitions and experimental validation. ACT and RFT are part of an even larger movement, named Contextual Behavioral Sciences (CBS), which proposes a reticulated model to produce knowledge, in which basic and applied research evolve independently, but in continuous interaction. This article discusses the research methods adopted to define, investigate and approximate one of the main therapeutic techniques of ACT, named by the middle-level term cognitive defusion, of the basic behavioral processes. The practical and experimental problems arising from these strategies of investigation are analyzed critically. Finally, new directions and experimental strategies are proposed for the investigation and definition of cognitive defusion.